APLIKASI MOBILE PERPUSTAKAAN SEKOLAH - Johan, Riche Cynthia; Silvana, Hana; Sulistyo, Holin (PEDAGOGIA, 2016)
Developing a school library is now a priority to determine the progress of literacy every individual in the ecosystem of the school. Information and communication technology to be triggered in providing easy access to information, including access to the library. This research studies; First, the draft form of a mobile applications based school library, called library apps. second, application adaptation procedure in the school library. research approach using design and development, with a pilot primary school library developed an online public library catalog which has been owned by the school, was developed using the basic ingredients Slims database previously accessible via http://perpustakaansd.labschool.upi.edu